Ontogenetic Oxycodone Exposure Affects Early Life Communicative Behaviors, Sensorimotor Reflexes, and Weight Trajectory in Mice - Minakova, Elena; Sarafinovska, Simona; Mikati, Marwa O.; Barclay, Kia M.; McCullough, Katherine B.; Dougherty, Joseph D.; Al-Hasani, Ream; Maloney, Susan E. (Frontiers in Behavioral Neuroscience, 2021)
Nation-wide, opioid misuse among pregnant women has risen 4-fold from 1999 to 2014, with commensurate increase in neonates hospitalized for Neonatal Abstinence Syndrome (NAS). NAS occurs when a fetus exposed to opioids in utero goes into rapid withdrawal after birth. NAS treatment via continued postnatal opioid exposure has been suggested to worsen neurodevelopmental outcomes. We developed a novel model to characterize the impact of in utero and prolonged postnatal oxycodone (Oxy) exposure on early behavior and development. Via subcutaneous pump implanted before breeding, C57BL/6J dams were infused with Oxy at 10 mg/kg/day from conception through pup-weaning. At birth, in utero oxy-exposed pups were either cross-fostered (paired with non-oxy exposed dams) to model opioid abstinence (in utero Oxy) or reared by their biological dams still receiving Oxy to model continued postnatal opioid exposure (prolonged Oxy). Offspring from vehicle-exposed dams served as cross-fostered (in utero Veh) or biologically-reared (prolonged Veh) controls. In utero Oxy exposure resulted in sex-dependent weight reductions and altered spectrotemporal features of isolation-induced ultrasonic vocalization (USV). Meanwhile, prolonged Oxy pups exhibited reduced weight and sex-differential delays in righting reflex. Specifically, prolonged Oxy female offspring exhibited increased latency to righting reflex. Prolonged Oxy pups also showed decreases in number of USV calls, and changes to spectrotemporal USV features. Overall, ontogenetic Oxy exposure was associated with impaired attainment of gross and sensorimotor milestones, as well as alterations in communication and affective behaviors, indicating a need for therapeutic interventions. The model developed here will enable studies of withdrawal physiology and opioid-mediated mechanisms underlying these neurodevelopmental deficits.